5PSQ-007 Impact of PUIzzle, a playful educational tool on high-alert medications on healthcare professionals' knowledge: what's new and what's left?. Issue 1 (23rd March 2023) - Chen, E; Lamand, V; Catala, L; Caré, W; Nielly, H; Broncard, C; Reynaud, B; Antoine, AL
Abstract : Background and Importance: High-alert medications (HAMs) have higher risks of causing harm to patients. To prevent this, our hospital pharmacy trained 147 healthcare professionals (HCPs) on this topic using a fun educational tool in puzzle form: PUIzzle (PUI is the French acronym for internal use pharmacy), which has significantly improved short-term knowledge on HAMs. However, its impact on long-term knowledge retention is not known. 1 Aim and Objectives: To evaluate PUIzzle's impact on HCPs' knowledge retention and its contribution to professional practices. Material and Methods: Our monocentric study took place in a 300-bed hospital in Paris region (France) between January and August 2022. No ethical approval for the study was requested. HCPs' knowledge was assessed with a self-questionnaire administered 3 weeks after the training (3WAT). The first part focused on professional practices. The second part was identical to the pre- and post-training knowledge questionnaire, to compare the scores of the pre-training (PrT), post-training (PoT) and 3WAT questionnaires. The third part had five other questions on HAMs. Results: Of the 141 eligible HCPs, 60 completed the 3WAT (31 nurses, 13 pharmacy technicians, 5 paramedical students, 4 caregivers, 6 healthcare students and 1 pharmacist) in a mean time of 3.6 months (σ=1.37), 48 were lost to follow-up and 33 did not respond. Fifty-two (87%) HCPs could situate one of the two HAMs' location list, and 44 (75%) could identify HAMs on the prescription software. Most changes in practice were observed at the prescribing level (n=31; 52%). HCPs declared being more attentive to HAMs' labelling. The mean score of PrT, PoT and 3WAT' second part were respectively 1.1/5 (σ=0.04), 3.1/5 (σ=0.14) and 2.5/5 (σ=0.33). A significant improvement between PrT and 3WAT (p<0.03) and a non-statistical decrease between PoT and 3WAT (p<0.17) were observed. The 3WAT's third part mean score was identical to the second one (σ=0.27). Conclusion and Relevance: PUIzzle's impact is positive on HCPs' practices and overall knowledge retention on HAMs. Therefore, our hospital will organise regular training sessions, and this training will be transposed into continuing professional education. References and/or Acknowledgements: 1. E. CHEN, 2022, Design of a fun educational tool for training on high-alert medications and evaluation of its impact on healthcare professionals' knowledge, pharmacy thesis, Paris-Cité University, France. Conflict of Interest: No conflict of interest